Difficulties Differentiating Between Basal Cell Carcinoma and Trichoepithelioma: A Case Report - Nurusshofa, Zahra; irena ujianti (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2021)
Background. Basal cell carcinoma (BCC) is the most common type of malignant skin tumor with basal cell differentiation. Trichoepithelioma (TE), however, is a rare benign skin tumor with follicular differentiation. Both types of tumor have commonalities in terms of clinical and histopathological features. Some cases, in fact, require ancillary studies to distinguish between the two. Confusing the two tumors may result in different future outcomes for the patient, due to their vastly different prognoses and treatments. This case report outlines two different cases, and discusses how to distinguish between the two types of tumor without the use of an ancillary study.Method. We examined the cases of one patient with basal cell carcinoma and one patient with trichoepithelioma, comparing their clinical manifestations and characteristic histological features.Results. Trichoepithelioma and BCC share several overlapping histopathological features. Trichoepithelioma and BCC share several overlapping histopathological features. The TE in this case report also exhibited a nodular pattern, connection to the epidermis, stromal cleft, and prominent nuclear palisading, which are more commonly found in BCC. However, scanty mitotic activity, the presence of non-atypia cells, and symmetry of the lesion, are favor TE.Conclusion. Differentiation between BCC and TE is only possible using cytomorphological assessment with a high-power field of view.